PU.1 controls the expression of long noncoding RNA HOTAIRM1 during granulocytic differentiation. Issue 1 (December 2016) - Wei, Shuyong; Zhao, Ming; Wang, Xiaoling; Li, Yizhen; Wang, Kankan
Abstract Background Long noncoding RNA HOX antisense intergenic RNA myeloid 1 (HOTAIRM1) has been characterized as a critical factor in all-trans retinoic acid (ATRA)-induced differentiation of acute promyelocytic leukemia (APL) cells. However, the essential transcription factor for gene expression of HOTAIRM1 is still unknown. Findings Chromatin immunoprecipitation (ChIP) assays revealed that PU.1 constitutively bound to the regulatory region ofHOTAIRM1 . Co-expression of PU.1 led to the transactivation of the regulatory region ofHOTAIRM1 in a reporter assay. Detailed analysis showed that two PU.1 motifs, which were located around +1100 bp downstream of the transcriptional start site of theHOTAIRM1 promoter, were responsible for the PU.1-dependent transactivation. The induction of HOTAIRM1 by ATRA was dependent on PU.1, and ectopic expression of PU.1 significantly up-regulated HOTAIRM1. Furthermore, low HOTAIRM1 expression was observed in APL cells, which was attributed to the reduced PU.1 expression rather than the repression by PML-RARα via the direct binding. Conclusion PU.1 directly activates the expression of HOTAIRM1 through binding to the regulatory region ofHOTAIRM1 during granulocytic differentiation. The reduced PU.1 expression, rather than PML-RARα itself, results in the low expression of HOTAIRM1 in APL cells. Our findings enrich the knowledge on the regulation of lncRNAs and the underlying mechanisms of the abnormal expression of lncRNAs involved in APL.